Studi Fenomenologi Mekanisme Koping Penyitas Covid 19 Saat Didiagnosis Positif Covid 19 - Yafet Pradikatama; Ellia Ariesti; M. Ali Sodikin (Jurnal Ilmu Kesehatan MAKIA, 2022)
ABSTRACT In 2020 the world experienced a Covid-19 pandemic, and this affected all aspects of life, especially health. The impact in the world of health is the number of people infected with the Corona virus. This pandemic makes some people experience fear, where the mass media reports a lot about deaths due to being infected with Covid. The existence of this phenomenon shows that it is necessary to conduct a study on how this Covid-19 survivor responds to his illness and survives until he is declared cured by the doctor. Research design: Qualitative, Research participants: Covid-19 survivors who have been declared cured. Results: 4 sub themes were found which resulted in 2 themes, namely: positive thinking and adapting to current circumstances. Conclusion: Participants were able to get through a critical period because they have adaptive internal and external coping mechanisms, so they can survive in a balanced state, both physically and psychologically. In the end, the participants were able to return to health, and were able to do the same activities as before the illness. Keywords: Individual Coping Mechanisms, Survivors of Covid 19, Experience